A latent class analysis of PTSD symptoms among inner city primary care patients. (March 2018) - Rahman, AKM Fazlur; Manatunga, Amita; Guo, Ying; Peng, Limin; Warnock, Megan; Ressler, Kerry J.; Jovanovic, Tanja
Abstract: Objectives: Examine evidence for different subclasses of posttraumatic stress disorder (PTSD) symptoms in a sample of trauma exposed, low-income, predominantly African American men and women. Assess the relationship between PTSD subclasses with major depressive disorder (MDD) and types of trauma experienced. Method: Latent class analysis (LCA) using a multivariate normal mixture model on the 17-item PTSD Symptom Scale (PSS) was used to identify latent subclasses of PTSD symptoms (N = 5063). Results: LCA suggested four subclasses of PTSD symptoms: (1) High severity and comorbidity (n = 932, 92.2% current PTSD, 88.7% MDD, 82% both), characterized by high PTSD symptoms, depression, and comorbidity of PTSD and MDD; (2) Moderate severity (n = 1179, 56.5% current PTSD, 53.9% MDD, 34.5% both), which had high avoidance and hyper-vigilance symptoms compared to the other symptoms; (3) Low PTSD and high depression (n = 657, 12.8% current PTSD, 49.9% MDD, 8.8% both) which had high insomnia but otherwise low PTSD symptoms and high depression; and (4) Resilient (n = 2295, 2.0% current PTSD, 16.4% MDD, and 0.6% both) characterized by low mean scores on all PTSD symptoms and depression. Conclusions: The results suggest avoidance and hyper-vigilance are important symptoms in PTSD development and insomnia may be an important indicator for depression. The combination of severe insomnia, avoidance, and hyper-vigilance may be key symptoms for comorbidity of PTSD and MDD. Future studies should focus on these symptoms to better target people at high risk for developing PTSD or MDD.